New Possible Surgical Approaches for the Submammary Adipofascial Flap Based on Its Arterial Supply. (29th September 2016) - Elzawawy, Ehab M.; Kelada, Melad N.; Al Karmouty, Ahmed F.
Abstract : Introduction . Submammary adipofascial flap (SMAF) is a valuable option for replacement of the inferior portion of the breast. It is particularly useful for reconstruction of partial mastectomy defects. It is also used to cover breast implants. Most surgeons base this flap cranially on the submammary skin crease, reflecting it back onto the breast. The blood vessels supplying this flap are not well defined, and the harvest of the flap may be compromised due to its uncertain vascularity. The aim of the work was to identify perforator vessels supplying SMAF and define their origin, site, diameter, and length. Materials and Methods . The flap was designed and dissected on both sides in 10 female cadavers. SMAF outline was 10 cm in length and 7 cm in width. The flap was raised carefully from below upwards to identify the perforator vessels supplying it from all directions. These vessels were counted and the following measurements were taken using Vernier caliper: diameter, total length, length inside the flap, and distance below the submammary skin crease. Conclusions . The perforators at the lateral part of the flap took origin from the lateral thoracic, thoracodorsal, and intercostal vessels. They were significantly larger, longer, and of multiple origins than those on the medial part of the flap and this suggests that laterally based flaps will have better blood supply, better viability, and more promising prognosis. Both approaches, medially based and laterally based SMAF, carry a better prognosis and lesser chance for future fat necrosis than the classical cranially based flap.